Penerapan Model Think Talk Write Dengan Kartu Soal Dalam Peningkatan Pembelajaran Matematika Pada Siswa Sekolah Dasar - Supriyadi, Supriyadi (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2024)
The aim of this research is to describe the steps for implementing the Think Talk Write model with question card media in improving Mathematics learning about comparisons and improving Mathematics learning about comparisons through applying the Think Talk Write model with question card media. This research is classroom action research (PTK). The subjects in this research were class V students of Al-Latif SD Muhammadiyah 9 Malang, totaling 25 students consisting of 10 female students and 15 male students. Data collection techniques in research are divided into two types, namely test and non-test. The data analysis technique used is qualitative descriptive analysis and quantitative descriptive analysis. The results of the research show that the application of the Think Talk Write model using question cards is carried out in the following steps: (a) the teacher forms groups of 4-5 students, (b) students are given problems in the form of questions or LKPD by the teacher, (c) students read the questions and think about possible answers by making notes (think), (d) the teacher asks students to discuss possible answers and determine the group's opinion (talk), (e) students write opinions resulting from group discussions in their own language (write), (f) students present the results of group discussions are then discussed in class, (g) the teacher and students conclude the lesson material. The Think Talk Write implementation model using question cards can improve mathematics learning about mathematics for fifth grade students at SD Muhammadiyah 9 Malang. The conclusion of this research is that the application of the Think Talk Write model using question cards can improve mathematics learning about mathematics for fifth grade students at SD Muhammadiyah 9 Malang.